QUALITY LEVEL-RELATED DIFFERENCES IN SELECTED MORPHOLOGICAL BODY CHARACTERISTICS AND MOTOR ABILITIES OF GOALKEEPERS IN TEAM HANDBALL - Marko Šibila; Igor Justin; Maja Pori; Tanja Kajtna; Primož Pori (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of the present study is to identify the quality level-related differences between two groups of team handball goalkeepers in selected morphological body characteristics and motor abilities. A group of 36 senior goalkeepers who were members of first and second Slovenian handball league clubs (age: 22,6 ± 5,4 yr, height: 185,8 ± 4,7 cm, body weight: 88,7 ± 9,1 kg, training experience: 11,8 ± 4,8 yr) participated in the present study. The goalkeepers were divided in two groups, according to their competition level. The sample of variables consisted of age and competition experience data, four morphological body characteristics and of six motor ability tests. In order to determine differences between two groups of goalkeepers in selected morphologic and motor variables a one-way analysis of variance (one-way ANOVA) was employed. Findings of the present study indicate existing of quality level-related differences between two groups of team handball goalkeepers in selected morphological body characteristics and motor abilities. Further individualization and careful planning of training process of the goalkeepers is essential if we want to improve for goalkeepers' important motor abilities and morphological body characteristics.